2013
DOI: 10.1080/00223891.2013.821074
|View full text |Cite
|
Sign up to set email alerts
|

Openness in Cross-Cultural Work Settings: A Multicountry Study of Expatriates

Abstract: Openness plays an important role in determining what kind of experiences individuals seek out not only in their personal lives, but also in work environments. The objectives of this study were (a) to examine the influence of openness and its facets on the decision to work abroad and (b) to study whether employees' openness relates to cross-cultural adjustment as well as job and life satisfaction. We investigated these questions among a sample of 2,096 expatriates. In addition to self-reports of openness and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The use of meta-analysis with our multi-country primary samples helped us reach conclusions regarding generalizable effects by correcting for the biasing influence of sampling and measurement error. Direct replications using such large numbers of samples in different cultural contexts are extraordinarily scarce in organizational behavior research (see Spector et al, 2001 ; Albrecht et al, 2014 , for two rare exceptions). In sum, the present study not only provides the first investigation of age differences in this important new performance domain, but does so at a scale that is typically only matched in quantitative summaries spanning several decades of published research.…”
Section: Discussionmentioning
confidence: 99%
“…The use of meta-analysis with our multi-country primary samples helped us reach conclusions regarding generalizable effects by correcting for the biasing influence of sampling and measurement error. Direct replications using such large numbers of samples in different cultural contexts are extraordinarily scarce in organizational behavior research (see Spector et al, 2001 ; Albrecht et al, 2014 , for two rare exceptions). In sum, the present study not only provides the first investigation of age differences in this important new performance domain, but does so at a scale that is typically only matched in quantitative summaries spanning several decades of published research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that individuals may react differently to cultural diversity in their social environment, leading some to be better able to communicate effectively across cultural boundaries and adjust more successfully to intercultural situations [1][2][3]. A significant predictor of these intercultural competences is personality [4][5][6]. Through meta-analysis [7], it was established that domain specific personality traits, such as cultural empathy and cross-cultural self-efficacy, are better predictors of intercultural effectiveness than more general personality traits such as the Big Five [8].…”
Section: Introductionmentioning
confidence: 99%
“…Stable competencies or personality traits – those that are unique to the expatriate and tend to remain relatively stable within‐person across time – were not. Despite this, a large body of research has since emerged aimed at understanding the impact of personality traits on expatriate adjustment (e.g., Albrecht, Dilchert, Deller, & Paulus, ; Caligiuri, , 2000a; Huang, Chi, & Lawler, ; Shaffer, Harrison, Gregersen, Black, & Ferzandi, ; Tsang, ).…”
Section: Introductionmentioning
confidence: 99%